Duration of therapy of ventilator-associated pneumonia. Issue 2 (April 2016) - Dimopoulos, George; Matthaiou, Dimitrios K.
Abstract : Purpose of review: Ventilator-associated pneumonia (VAP) is a major cause of morbidity and mortality in the critical care setting. It incurs great additional cost and the antibiotics prescribed for patients with VAP account for the majority of total antibiotic prescriptions. The increased cost of VAP as well as the emergence of antimicrobial resistance and the potential adverse events because of treatment indicate that the application of shorter antibiotic regimens for the treatment of VAP poses as a one-way choice. Recent findings: According to the findings of relevant randomized controlled trials, patients receiving short-course regimens for the treatment of VAP have significantly more antibiotic-free days without any negative impact on mortality. Additionally, no other differences were found regarding other secondary outcomes. However, there were higher relapse rates in patients with VAP because of nonfermenting Gram-negative bacilli and there was a lower emergence of multidrug-resistant pathogens. Summary: The shortening of the duration of treatment for VAP is promising, as long as a holistic approach that combines methods ensuring the adequate sterilization of septic foci, the optimization of antibiotic levels, the multifaceted delivery of antimicrobials in the lung and the usage of biomarkers that allow the monitoring of the disease course and the effectiveness of administered treatment are incorporated in clinical practice.